Grain boundary, electrical transport and thermoelectric properties of the ultra-high rGO amount of C12A7-rGO composites - Maneesai, Keerati; Thongkam, Montree; Sriwong, Chaval; Ruttanapun, Chesta (My University, 2024)
The Ca12Al14O33 ceramic (C12A7) and reduced graphene oxide (rGO) composite which an ultra-high amount (i.e., 40, 50, 60, and 70 wt%) of rGO (ultra-high amount C12A7/rGO composite) were synthesized by a solid-state reaction process. After the hydraulic press, the heat treatment in the temperature range of 773 K under the argon environment had been performed with the composite pellets for 30 min. XRD results of the C12A7 and all the ultra-high amount C12A7/rGO composites indicated a pure phase of C12A7 ceramic. Raman spectra confirmed the existence of rGO content in all the ultra-high amount C12A7/rGO composites. Raman peaks also suggested reduction of the free O22− and O2− ions from the framework of the ultra-high amount C12A7/rGO composites. SEM image presented the homogeneous grain boundary interface after the heat treatment at 773 K of the C12A7 wrapped by the rGO sheet, the agglomerated rGO sheet, and the rough interface stack of rGO sheets. UV-VIS spectroscopy presented the absorption behavior, direct energy gap, and indirect energy gap modifications of the ultra-high amount C12A7/rGO composites. Electrical conductivity of the ultra-high amount C12A7/rGO composites illustrated larger than 108 times improvement with temperature independence. Range of −5 to −17 μV/K, temperature dependence, and increased with rGO content increasing Seebeck coefficient were reported. Thermal conductivity of the ultra-high amount C12A7/rGO composites was increased with the rGO content increasing. Both the Power factor (PF) and the figure of merit (ZT) of the ultra-high amount C12A7/rGO composites were temperature dependent and were increased with the rGO content increasing, within the range of 0.4 μW/m.K2 of PF and the range of 3x10−4 of ZT, respectively. These experimental results verified grain boundary, modified energy band, electrical transport properties and thermoelectric properties of C12A7/rGO composites loading with ultra-high content rGO
Keywords: Agglomeration; C12A7 and ultra-high amount rGO composites; Electrical transport properties; Grain boundary; Thermoelectric properties